MicroRNA‐221 overexpression accelerates hepatocyte proliferation during liver regeneration123. Issue 1 (7th January 2013) - Yuan, Qinggong; Loya, Komal; Rani, Bhavna; Möbus, Selina; Balakrishnan, Asha; Lamle, Jutta; Cathomen, Toni; Vogel, Arndt; Manns, Michael P.; Ott, Michael; Cantz, Tobias; Sharma, Amar Deep
Abstract The tightly controlled replication of hepatocytes in liver regeneration and uncontrolled proliferation of tumor cells in hepatocellular carcinoma (HCC) are often modulated by common regulatory pathways. Several microRNAs (miRNAs) are involved in HCC progression by modulating posttranscriptional expression of multiple target genes. miR‐221, which is frequently up‐regulated in HCCs, delays fulminant liver failure in mice by inhibiting apoptosis, indicating a pleiotropic role of miR‐221 in hepatocytes. Here, we hypothesize that modulation of miR‐221 targets in primary hepatocytes enhances proliferation, providing novel clues for enhanced liver regeneration. We demonstrate that miR‐221 enhances proliferation of in vitro cultivated primary hepatocytes. Furthermore, applying two‐thirds partial hepatectomy as a surgically induced liver regeneration model we show that adeno‐associated virus‐mediated overexpression of miR‐221 in the mouse liver also accelerates hepatocyte proliferation in vivo. miR‐221 overexpression leads to rapid S‐phase entry of hepatocytes during liver regeneration. In addition to the known targets p27 and p57, we identify Aryl hydrocarbon nuclear translocator (Arnt) messenger RNA (mRNA) as a novel target of miR‐221, which contributes to the pro‐proliferative activity of miR‐221. Conclusion: miR‐221 overexpression accelerates hepatocyte proliferation. Pharmacological intervention targeting miR‐221 may thus be therapeutically beneficial in liver failure by preventing apoptosis and by inducing liver regeneration. (HEPATOLOGY 2013;)